Dynamic Analysis of a Planar Hydraulic Rock-Breaker Mechanism with Multiple Clearance Joints - Ke Chen; Guojun Zhang; Rui Wu; Li Wang; Hongmei Zheng; Shunhua Chen (Shock and Vibration)
Clearance exists in the joint of a mechanism because of the assemblage, manufacturing tolerances, wear, and other conditions, and it is a focus of research in the field of multibody dynamics. This study built a planar hydraulic rock-breaker model with multiple joint clearances by combining the hydraulic cylinder model, the clearance joints based on the Lankarani–Nikravesh contact force model, and the Lagrange multiplier method. Dynamic simulation results indicated that multiple clearance joints can degrade the dynamic responses of a rock-breaker model, which can be decomposed to rapid vibrations and slow movements. The rapid vibrations are excited by coupling the spring-mass system of hydraulic cylinder and clearances. The effects of the clearance size, input force, damping coefficient, and friction on the dynamic behaviour of the rock-breaker mechanism are also investigated. The friction could reduce the rapid vibration state significantly, which is feasible for practical engineering applications. As compared with the traditional models without clearances, the present model provides not only better predictions for the theoretical study of the hydraulic rock-breaker but also useful guidance for reducing the vibrations of the hydraulic rock-breaker in practical engineering applications.